Efficacy of Integrative Behavioural Couples Therapy and Cognitive Behavioural Therapy in Reducing Conflict and Violence-Related Marital Distress - Doh Fia, Stephen (European Scientific Journal, ESJ, 2020)
This study investigated the ability of Integrative Behavioural Couples Therapy and Cognitive Behavioural Therapy in reducing conflict-related and violence-related marital distress among couples in the Church of Pentecost in the Cape Coast Metropolis in the Central Region of Ghana. The researcher employed a quantitative research method, using a pre-test, post-test control group, a kind of quasi-experimental research design. The researcher selected 60 respondents who were severely distressed out of 215 married couples using a compendium of instruments on Conceptualising and Measuring “Healthy Marriages” for Empirical Research and Evaluation Studies (Task One Part II). Participants were put into three groups of 10 couples each, two for the treatment groups and the third one for the control group. The data were analysed using means, standard deviations and two-way mixed ANOVA. The results showed that both therapies reduced conflict-related and violencerelated marital distress. However, Integrative Behavioural Couples Therapy was more effective than Cognitive Behavioural Therapy.